2008
DOI: 10.1182/blood-2008-04-150508
|View full text |Cite
|
Sign up to set email alerts
|

FLT3 ligand and not TSLP is the key regulator of IL-7–independent B-1 and B-2 B lymphopoiesis

Abstract: Phenotypically and functionally distinct progenitors and developmental pathways have been proposed to exist for fetally derived B-1 and conventional B-2 cells. Although IL-7 appears to be the primary cytokine regulator of fetal and adult B lymphopoiesis in mice, considerable fetal B lymphopoiesis and postnatal B cells are sustained in the absence of IL-7; in humans, B-cell generation is suggested to be largely IL-7-independent, as severe combined immune-deficient patients with IL-7 deficiency appear to have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
37
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 35 publications
2
37
1
Order By: Relevance
“…Few molecules have been reported to act in such a way, with IL-7 and IL-7R being the prototypical examples (26). Because Flt3 (also called FLK2) signal can compensate IL-7 signal in the fetal liver, B lymphopoiesis is independent of IL-7 in the fetal liver, which is indispensable for that in bone marrow (27,28). However, no study has shown that fetal and adult NK cell development is regulated by distinct cytokine signal or transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Few molecules have been reported to act in such a way, with IL-7 and IL-7R being the prototypical examples (26). Because Flt3 (also called FLK2) signal can compensate IL-7 signal in the fetal liver, B lymphopoiesis is independent of IL-7 in the fetal liver, which is indispensable for that in bone marrow (27,28). However, no study has shown that fetal and adult NK cell development is regulated by distinct cytokine signal or transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…We do not exclude the possibility, however, that TSLP or IL-7 in combination with other growth factors are able to induce proliferation of HSC, but this remains to be addressed. In the absence of IL-7R-mediated signaling, a vital role for FLT3L has been implicated to drive mouse fetal B-cell development [7,39]. The importance of FLT3L has not been directly tested in human, but it might explain why severe combined immune-deficient patients with IL-7R deficiency appear to have normal B-cell numbers [2,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…IL-7Ra 2/2 mice have been previously shown to be defective in adult pro-B and pre-B cell development but have normal pre-pro-B development (13,14). Overexpression of TSLP can induce the expansion of progenitor B cells in the bone marrow (15); however, TSLPR 2/2 mice have no reported defect in B cell development (16), suggesting it has a nonessential role in normal B cell development. There are three conserved tyrosines in the cytoplasmic domain of IL-7Ra found in all mammals.…”
mentioning
confidence: 97%